Electricity supply side development in Uzbekistan - AVAZOV, Shokhrukh Normurodovich (KDI School, 2015)
As a transitioning economy, the energy sector of Uzbekistan is expected to play a pivotal role in the development of a market-based economy in the future. Uzbekistan has enough resources to develop its energy sector, including electricity sector. However, there are organizational and institutional issues that remain critical challenges to the modern economy and society. This study looks at the South Korean experience of the development of its electricity sector following the Korean War, including notable reforms and projects implemented throughout its evolution, through comparative study with Uzbekistan’s development history following independence. In identifying the organizational and structural challenges of Uzbekistan’s electricity sector and associated source factors, cross-national comparison method and a case study of South Korea will be used whilst suggesting solutions based on the South Korean experience. Detailed analysis shows that the Five Year Power Expansion Plan, the establishment of required institutions and Saemaul Undong (New Village Movement) of South Korean Government were implemented effectively and led to the improvement of the energy sector, infrastructure and quality of life of people. Moreover, the privatization of the national power corporation – KEPCO – had a positive impact on the improvement of the power of the market in South Korea. I suggest best practices and reforms that Uzbekistan can adopt from South Korea.
Thesis(Master) --KDI School:Master of Development Policy,2015